A Study to Assess the Effect of Planned Teaching Program on the Knowledge Regarding Alzheimer’s Disease and Home Care Management among the Care Givers of Elderly in Selected Rural Area - Pednekar, Sneha; Rawade, Manisha (Indian Journal of Nursing Sciences, 2024)
Introduction: Alzheimer’s disease (AD) is a progressive brain disorder that damage and eventually destroys brain cells, leading to memory loss and changes in thinking and other brain functions. Ultimately, Alzheimer’s is fatal, and at present, there is no cure. India’s dementia and Alzheimer’s burden is forecast to reach almost 7.5 million by the end of 2030. The knowledge about the disease should be utilized to prevent or delay occurrence of disease and also to find out the symptoms of the disease at the earliest for reception of the quality care. Hence, the researcher felt a need to provide a planned teaching programme for elderly person’s caregiver to create awareness on preventive aspects of AD. Aim: The aim of study was to assess the effectiveness of planned teaching program on the knowledge and home care management regarding AD among the care givers in selected rural area. Subjects and Methods: One group pre- and post-test research design was adopted, where the group was assessed with the structured questionnaire before and after. A structured teaching program and questionnaire administered to asses knowledge and management of AD among care giver. Results: we observed that knowledge measured after planned teaching was significantly better (P ≤ 0.05). There were no association of knowledge with any of demographic variables. Conclusion: Planned teaching was effective measure to improve knowledge and home care management regarding AD among the care givers in selected rural area.